Intermittent claudication among smokers - Yathish, T. R.; Annamallai, N.; Shankar, V. (Journal of Institute of Medicine Nepal, 2010)
Introduction: Peripheral artery disease with intermittent claudication is an important cause of morbidity and mortality. Cigarette smoking is thought to be major risk factor. Currently, up to 2% of all deaths are attributable to peripheral artery disease and its complication. The economic burden associated with peripheral artery disease is also substantial. There are still significant gaps in the current understanding of the epidemiology and burden of peripheral artery disease at the population level. Methods: The aim of this study was to study intermittent claudication through survey by questionnaire method and to study risk factors of tobacco by evaluating the relationship between smokers and intermittent claudication using well accepted Rose intermittent claudication and smoking questionnaire method. This observational, descriptive, cross-sectional study was conducted in the teaching hospital of R.L. Jalappa Hospital of Sri Devaraj Urs medical college, Tamaka, Kolar, Karnataka, India during January 2004 to July 2004. A total of 130 adult men above the age of 30 years who visited the hospital with pain in the lower limbs constituted the materials for the present study. They were categorized into smokers and non-smokers. Each case was examined for lower limbs in detail and their findings were noted. Results: Participants in the group with leg pain on exertion and rest were nearly 92. Among 90 smokers, 80 had the classic symptom of intermittent claudication which started in the third decade of life whereas out of 40 non-smokers, only 12 had intermittent claudication which started after the fifth decade of life. Conclusions: Smoking not only results in early onset of intermittent claudication but also increases the risk of development of intermittent claudication by more than 80%. Keywords: Intermittent claudication, rose intermittent claudication and smoking questionnaire, smoking DOI: 10.3126/joim.v31i3.2991 Journal of Institute of Medicine, December, 2009; 31(3) 21-26